A practical guide to thiopurine prescribing and monitoring in IBD. Issue 1 (29th August 2016) - Warner, Ben; Johnston, Emma; Arenas-Hernandez, Monica; Marinaki, Anthony; Irving, Peter; Sanderson, Jeremy
Abstract : Thiopurines are often the mainstay of treatment for many patients with inflammatory bowel disease. As such, a general understanding of the evidence behind their use and of their metabolism is extremely useful in clinical practice. This review gives a practical overview of thiopurine metabolism, the importance of thiopurine S-methyltransferase testing prior to the start of therapy and the monitoring of thioguanine nucleotide levels while on treatment, guiding a personalised approach to optimising thiopurine therapy.